2007
DOI: 10.1136/oem.2007.034298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of talc dust on respiratory health: results of a longitudinal survey of 378 French and Austrian talc workers

Abstract: Although early exposure levels to talc as assessed at inclusion were associated with decreased lung function and an increased prevalence of small radiological opacities, there was no evidence of detrimental effects of talc exposure, as assessed within the study period, on lung function and small radiological opacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Studies examining radiological, lung function, and clinical (eg, wheezing, coughing, bronchitis) parameters in talc miners and millers and rubber workers found some statistically significant decreases in lung function. 97,103 -107…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Studies examining radiological, lung function, and clinical (eg, wheezing, coughing, bronchitis) parameters in talc miners and millers and rubber workers found some statistically significant decreases in lung function. 97,103 -107…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…As the participants were all healthy subjects, the basic levels of FVC, FEV 1.0 , and FEV 1.0 /FVC were in the normal range, and they possibly had not been changed in the short-term observation; Wild P et al 16 showed FVC, FEV 1.0 of the talc workers only decreased by 7.71, 6.11 mL per year·mg/m 3 . Meanwhile, application of the suitable protective equipments could prevent the large particulates from depositing in the extrathoracic regions and affecting the function of the airways.…”
Section: Discussionmentioning
confidence: 96%
“…14 Also, in occupational population, a dose-response relationship between cumulative wood dust exposure and percent annual decrease in FEV 1.0 was suggested for female workers 15 at the median level of 3.75 mg·year/m 3 for cumulative wood dust exposure, as for talc workers. 16 As we know, TiO 2 , black carbon, and talc are defined as poorly soluble, low toxicity dust, 17 and they have similar properties. Referring to the results of research on the health effects of black carbon and talc, combined with the role of particle size on the health effects, we determined to explore the cardiopulmonary effects of short-term occupational TiO 2 exposure on the basis of particles size distribution assessment in the workshop by a panel study.…”
mentioning
confidence: 99%
“…No studies on children Wild et al. ( 2008 ) Mandel et al. ( 2016 ) Clays, diamond, diatomite, Kyanite, lime, mica, rubber, sand and gravel, stone‐crushed, stone‐ dimension, sulfur No studies found Note : * indicates the studies that describe negative health effects of minerals on birth outcomes; References are cited next.…”
Section: Table A1mentioning
confidence: 99%